Swamedikasi Penggolongan Obat Melalui Brosur Untuk Menambah Knowledge Masyarakat - Wijayanti, Lumastari Ajeng; Djunaedi, Djunaedi; Nurhaedah, Nurhaedah; Pannyiwi, Rahmat; Surya, Sara; Akbar, Akbar; Latif, Farida (Barongko: Jurnal Ilmu Kesehatan, 2025)
Drugs are preparations or combinations of ingredients that are ready to be used to influence or investigate physiological systems or pathophysiological conditions in order to determine the diagnosis, prevention, healing, recovery, improvement, health and contraception. The purpose of this study was to determine the level of knowledge about drugs before and after providing drug information with leaflet media to the community. This research method is a type of experimental research, namely research conducted to determine the effects of the treatment of providing drug information with leaflet media to increase public knowledge with the form of one group pretest-posttest design, namely the pretest posttest design in a group. The results showed an increase in knowledge value after providing drug information in the form of leaflets. The conclusion of this study is that before the provision of drug information in the form of leaflets was in the low category with an average score of 52.77 ± 11.06 and after providing drug information in the form of leaflets, the level of respondent knowledge increased to the high knowledge category with an average score of 76.86 ± 8.62.